Evaluating Indirect Ecological Effects of Biological Control. Key Papers From the Symposium 'Indirect Ecological Effects in Bio 2000
DOI: 10.1079/9780851994536.0147
|View full text |Cite
|
Sign up to set email alerts
|

Rhinocyllus conicus : initial evaluation and subsequent ecological impacts in North America.

Abstract: Renewed debate over the risk of non-target effects in biological control reflects, in part, the recent quantification of direct and indirect ecological effects of the flowerhead weevil, Rhinocyllus conicus Frol., in North America. To help resolve the issue, we review the published data for R. conicus from both Europe and North America: pre-release (1961-1968), post-release (1969-1985) and more recen t (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999). Our aim was to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 65 publications
2
49
0
Order By: Relevance
“…First, capitulum diameter information is necessary to correct for differences in drying time and seed production (larger capitula produce more seeds). Second, florivory by R. conicus reduces the number of seeds available for release during wind tunnel trials (Gassmann and Louda 2001;Sezen 2007). Finally, both field VPD and precipitation information allow the effect of natural conditions in the field to be quantified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, capitulum diameter information is necessary to correct for differences in drying time and seed production (larger capitula produce more seeds). Second, florivory by R. conicus reduces the number of seeds available for release during wind tunnel trials (Gassmann and Louda 2001;Sezen 2007). Finally, both field VPD and precipitation information allow the effect of natural conditions in the field to be quantified.…”
Section: Discussionmentioning
confidence: 99%
“…(a biocontrol agent) were counted to quantify florivory in each capitulum. This damage is known to reduce seed production (Gassmann and Louda 2001;Sezen 2007).…”
Section: Capitulum Dissectionsmentioning
confidence: 99%
“…thistles, especially musk thistle, C. nutans L. (Zwölfer and Harris 1984;Gassmann and Louda 2001). The weevil oviposits on external bracts of developing flower heads, covering each egg with an obvious case of masticated plant tissue.…”
Section: Natural History and Backgroundmentioning
confidence: 99%
“…We used regression (PROC REG: SAS 1999) to identify the model with the lowest mean square error and fewest nonsignificant variables. We included as explanatory variables only those climate variables that our literature review indicated were likely to affect thistle development, or weevil activity, survival, or development (Rathcke and Lacey 1985;Tauber et al 1986;Tauber et al 1998;Gassmann and Louda 2001). For R. conicus egg cases per wavyleaf flower head, weevil abundance, and weevil-plant phenological synchrony, we examined both precipitation and GDD in the previous summer, previous autumn, preceding winter and spring; winter and spring relative humidity; and days until both last hard freeze and last freeze in spring.…”
Section: Influence Of Climatic Variablesmentioning
confidence: 99%
“…In the northern plains, it is a taprooted, short-lived, iterocarpic perennial (Great Plains Flora Association 1986). In Nebraska, C. undulatum bolts in mid to late May, begins flowering in early June, and disperses most seeds in late July (McCarty 1982, Louda 1998 (Zwölfer andHarris 1984, Gassmann andLouda 2001).…”
Section: Natural History Of Study System and Study Sitesmentioning
confidence: 99%